Effect of Learning Module with Setting Contextual Teaching and Learning to Increase the Understanding of Concepts - Putu Yulia Angga Dewi; Kadek Hengki Primayana (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
This study aims to analyze differences in conceptual understanding between students facilitated by learning modules with Contextual Teaching and Learning settings and direct learning models. This study was a quasi-experimental study using a pretest-posttest nonequivalent control groups design. . The data collected in this study are data understanding concepts with concept understanding tests. Then the concept understanding data was collected by concept understanding tests in the form of reasoned objective tests consisting of 19 items. Data on understanding concepts were analyzed descriptively using one-way analysis of variance. Research shows that understanding the concept of groups of students learning by facilitating learning modules containing Contextual Teaching and Learning is higher than the group of students who learn through direct learning models. Based on these findings it was concluded that there were differences in understanding of physics concepts between students facilitated by learning modules containing Contextual Teaching and Learning and direct learning models.